Biochemical Genetic Evidence for Fish Stocks in Lake Trout (Salvelinus namaycush), Bloater (Coregonus hoyi), and Brook Trout (Salvelinus frontalis) in the Great Lakes Region - DuVall, Brian M. (University of Wisconsin-Stevens Point, College of Natural Resources, 1983)
Electrophoretic analysis of polymorphic isoenzyme systems in lake trout (Salvelinus namaycush) from the Apostle Islands, Lake Superior, in the bloater (Coregonus hoyi) from the western region of Lake Michigan, and in brook trout (Salvelinus fontinalis) from a central Wisconsin stream and from a state hatchery, was carried out to determine if intraspecific genetic differences could be found as evidence of the existence of genetically discrete stocks in these three species. Lake trout liver tetrazolium oxidase allele frequencies were homogenous among three samples from different areas in the Apostle Islands region, but liver NADP dependent isocitrate dehydrogenase gamete frequencies were significantly different among these groups of lake trout. Bloater muscle glycerol-3-phosphate dehydrogenase allele frequencies were homogenous among five samples collected over the range from Algoma to Kenosha, Wisconsin. Bloater muscle isocitrate dehydrogenase allele frequencies differed among all sample pairs on the basis of a best-fit genetic model. The latter differences support data of the Wisconsin Department of Natural Resources on the possibility of separate stocks of bloaters based on different age composition data of samples from various areas of western Lake Michigan. Samples of brook trout from Brewer Creek, Juneau County, Wisconsin collected in the year before and after stocking was discontinued were compared genetically with hatchery fish from Langlade Hatchery, Langlade County, Wisconsin on the basis of malate dehydrogenase, glycerol-3-phosphate dehydrogenase, and lactate dehydrogenase. Allele frequencies were significantly different in at least one system among all three samples. Nei similarity indices indicated that the hatchery sample was most similar to the stream sample collected before stocking was discontinued and that the two stream samples, collected before stocking was discontinued were most dissimilar. These data indicate a genetic effect of stocking on stream population.